The Prevalence of Students and Teachers’ Ideas about Global Warming and the Use of Renewable Energy Technology - Laliyo, Lukman Abdul Rauf; Puluhulawa, Fenty U.; Eraku, Sunarty; Salimi, Yuszda K. (Journal of Environmental Accounting and Management, 2026)
This study aims to explore the prevalence of students’ and teachers’ ideas about global warming and the use of renewable energy technology in Gorontalo, Indonesia. Employing a non-experimental quantitative approach, the data were collected from 1522 respondents and analyzed with the WINSTEPS 3.73 Rasch software. This study reports that 97.6% and 76.08% of the respondents respectively understand the concepts of global warming and renewable energy from the internet (45%) and formal education (